Interaction of initial deficiency with centres of colouring in MgF2 crystals; International Conference "Vacuum ultraviolet spectroscopy and radiation interaction with condensed matter VUVS 2005" (Irkutsk, July 18-22, 2005) - Korepanov V. I. Vladimir Ivanovich (2005, 2005)
В фонде НТБ ТПУ отсутствует